Dual Induction of New Microbial Secondary Metabolites by Fungal Bacterial Co-cultivation - Wakefield, Jennifer; Hassan, Hossam M.; Jaspars, Marcel; Ebel, Rainer; Rateb, Mostafa E. (Frontiers in Microbiology, 2017)
The frequent re-isolation of known compounds is one of the major challenges in drug discovery. Many biosynthetic genes are not expressed under standard culture conditions, thus limiting the chemical diversity of microbial compounds that can be obtained through fermentation. On the other hand, the competition during co-cultivation of two or more different microorganisms in most cases leads to an enhanced production of constitutively present compounds or an accumulation of cryptic compounds that are not detected in axenic cultures of the producing strain under different fermentation conditions. Herein, we report the dual induction of newly detected bacterial and fungal metabolites by the co-cultivation of the marine-derived fungal isolate Aspergillus fumigatus MR2012 and two hyper-arid desert bacterial isolates Streptomyces leeuwenhoekii strain C34 and strain C58. Co-cultivation of the fungal isolate MR2012 with the bacterial strain C34 led to the production of luteoride D, a new luteoride derivative and pseurotin G, a new pseurotin derivative in addition to the production of terezine D and 11-O-methylpseurotin A which were not traced before from this fungal strain under different fermentation conditions. In addition to the previously detected metabolites in strain C34, the lasso peptide chaxapeptin was isolated under co-culture conditions. The gene cluster for the latter compound had been identified through genome scanning, but it had never been detected before in the axenic culture of strain C34. Furthermore, when the fungus MR2012 was co-cultivated with the bacterial strain C58, the main producer of chaxapeptin, the titre of this metabolite was doubled, while additionally the bacterial metabolite pentalenic acid was detected and isolated for the first time from this strain, whereas the major fungal metabolites that were produced under axenic culture were suppressed. Finally, fermentation of the MR2012 by itself led to the isolation of the new diketopiperazine metabolite named brevianamide X.